Diversity of Orchids in Shiureni Forest, Aadhikhola Rural Municipality, Syangja, Nepal - Kafle, Sapana; Pathak, Hom Nath (Himalayan Biodiversity, 2023)
The elevational gradient is one of the important factors that determine the distribution pattern of many wild ornamental plants. In this study, we explored the diversity of the orchid flora along different elevation gradients from Thumki to Thapley viewpoint in Siureni forest, Syangja, Nepal. The study was done by the transect walk method. In all 11 transect points altogether 25 orchid species were found belonging to 12 genera out of which 10 genera were of medicinal importance i.e., Acampe, Aerides, Calanthe, Coelogyne, Cymbidium, Dendrobium, Oberonia, Pholidota, Rhynchostylis, Vanda, etc. One of them was endemic orchid i.e., Oberonia nepalensis. The larger genera found were Bulbophyllum and Coelogyne with seven and three species respectively followed by Dendrobium, Rhynchostylis, Vanda, Aerides, Oberonia each with two species. The remaining genera had one species of each. This research output will be helpful in sustainable management and acquiring knowledge about the diversity of orchids in Aadhikhola Rural municipality, Syangja district, Gandaki Province, Central Nepal.